ÉTICA E EDUCAÇÃO AMBIENTAL NO CONTEXTO DE CRISE DAS SOCIEDADES MODERNAS - Souza Silva, Saulo Henrique; Alves, Adriana (Prometheus - Journal of Philosophy., 2020)
This article aims to investigate the general contours of the environmental crisis triggered by the advance of man's domination over nature, based on the basic premises of modern philosophy. The environmental crisis is understood by environmental ethics as the result of the predatory action of modern societies, mediated by the technique and the appropriation of natural goods. In this context of civilizational crisis, ethics and environmental education must contribute to the formation of ecological awareness, which is essential for the preservation of the conditions necessary for the maintenance of life.